La actividad física como alternativa para combatir la depresión en estudiantes de bachillerato de la institución “27 de febrero”, Loja 2023 - Carrion Hernandez, Daniel Alejandro (2024)
The present thesis investigates the relationship between physical activity and the reduction of depression symptoms in young adults. Depression is a common mental disorder that affects a large number of people worldwide, with significant consequences for health and well-being. The study was conducted using a mixed-methods approach, a randomized quasi-experimental design with two groups: an experimental group of 10 individuals who participated in a structured physical activity program, and a control group of 10 individuals who maintained their usual routine without changes. The sample consisted of 20 participants aged between 15 and 18 years, diagnosed with mild to moderate depression. At the beginning of the study, depressive symptoms were evaluated, initially in week 2, and again at the end of week 5, using the Beck Depression Scale, yielding highly positive results. Once these collected data were analyzed, a proposal was designed in which the experimental group engaged in physical activity sessions using various activities such as games, walks, aerobic exercises, and resistance training, tailored to the participants' preferences and fitness levels. After the implementation of the proposal, a post-test was administered, yielding results that demonstrated a significant reduction in depressive symptoms in the experimental group. Participants who engaged in the physical activity program experienced significant improvements in their mood, energy levels, and overall quality of life. Additionally, additional benefits were observed in self-esteem and body image perception. In conclusion, this study provides empirical evidence supporting the effectiveness of physical activity as a complementary therapeutic intervention for reducing depression symptoms in young adults. Keywords: Physical acivity, depression, education